Infant Hospitalizations and Fatalities Averted by the Maternal Pertussis Vaccination Program in England, 2012–2017: Post-implementation Economic Evaluation. (25th February 2020) - Sandmann, Frank; Jit, Mark; Andrews, Nick; Buckley, Hannah L; Campbell, Helen; Ribeiro, Sonia; Sile, Bersabeh; Stowe, Julia; Tessier, Elise; Ramsay, Mary; Choi, Yoon H; Amirthalingam, Gayatri
Abstract: In October 2012, a maternal pertussis vaccination program was implemented in England following an increased incidence and mortality in infants. We evaluated the cost-effectiveness of the program by comparing pertussis-related infant hospitalizations and deaths in 2012–2017 with nonvaccination scenarios. Despite considerable uncertainties, findings support the cost-effectiveness of the program.